Crossing barriers: the burden of inflammatory bowel disease across Western Europe - Aditi Kumar; Nuha Yassin; Alexandra Marley; Vittoria Bellato; Caterina Foppa; Gianluca Pellino; Pär Myrelid; Monica Millan; Beatriz Gros; Nicolas Avellaneda; Ignacio Catalan-Serra; Alaa El-Hussuna; et al. (Therapeutic Advances in Gastroenterology, 2023)
An estimated 2.5–3 million individuals (0.4%) in Europe are affected by inflammatory bowel disease (IBD). Whilst incidence rates for IBD are stabilising across Europe, the prevalence is rising and subsequently resulting in a significant cost to the healthcare system of an estimated 4.6–5.6 billion euros per year. Hospitalisation and surgical resection rates are generally on a downward trend, which is contrary to the rising cost of novel medication. This signifies a large part of healthcare cost and burden. Despite publicly funded healthcare systems in most European countries, there is still wide variation in how patients receive and/or pay for biologic medication. This review will provide an overview and discuss the different healthcare systems within Western Europe and the barriers that affect overall management of a changing IBD landscape, including differences to hospitalisation and surgical rates, access to medication and clinical trial participation and recruitment. This review will also discuss the importance of standardising IBD management to attain high-quality care for all patients with IBD.